The von Meyenburg complex (hamartoma of the bile duct) mimicking liver metastases - Vukmirović, Filip; Tomašević Vukmirović, Irena; Vukmirović, Mihailo (Vojnosanitetski pregled, 2017)
Background. Hamartomas of the bile duct (von Meyenburg complex) are benign lesions of the liver that may mimic liver metastases. They constituted histologically of cystic dilatations of the bile duct, encompassed by fibrous stroma. Case report. We report a 68-year-old male patient with whose gross, ultrasonic and MSCT appearance suggestive of multiple liver metastases. A diagnosis of von Meyenburg complex was made after histopathologic examination of the biopsy of the liver. Conclusion. von Meyenburg complex as uncommon entity and should be taken into consideration as a differential diagnosis of liver metastases.
Keywords: hamarthoma; bile ducts; diagnosis; differential; diagnostic techniques and procedures; biopsy